Integration Kano Model and E-Servqual to Evaluate Online Travel Agent Services in Bandung 2022 - Bethani Suryawardani; Dendi Gusnadi; Astri Wulandari; Dandy Marcelino (Jurnal Kawistara, 2022)
One of the integrated e-commerce models is online ticket selling. Many travel agents sell travel tickets for national or international destinations online through websites; one of them is Tiket.com, a popular travel agency in Indonesia. The intense competition in the internet-based service providing industry has, in fact, motivated this company to meet their customers’ needs and preferences with quality services; the goal is to increase the number of their service users. The purpose of this study is to identify aspects of user requirements by Tiket.com as an online travel agent service that need to be maintained and improved. This study combines two methods of measuring customer satisfaction, namely the Kano model and e-service quality. The identified customer needs, based on Voice of Customer, can be analyzed to increase satisfaction. The results of this study are grouped into the dimensions of e-service quality, i.e. reliability, responsiveness, fulfillment, ease of use, information, security, and efficiency. Using a combination of e-service quality and Kano Model, six attributes of True Customer Needs were acquired; five of them are recommended for improvement and one needs to be developed. Tiket.com are suggested to pay more attention to weak attributes that are included in the must be category because they are fundamental for the company's services. They are also advised to develop weak and strong attributes that are included in the attractive category because they can help the company increase their competitive advantage.